A comparison of head impact characteristics during elite men`s Rugby Union fifteens and sevens match play - Paiement, B.; Karton, C.; Gilchrist, M. D.; Hoshizaki, T. B. (Computer Methods in Biomechanics and Biomedical Engineering, 2026)
Different forms of rugby may pose distinct risks to head injury. Video of rugby match footage was analyzed using head impact magnitude, frequency, and time interval for 15s and 7s athletes. Impacts were reconstructed in laboratory, and finite element modeling was used to estimate maximum principal strain. No difference was found in impact frequency or time interval between the two forms. Significantly more head impacts of higher severity levels were documented during 7s. These findings provide objective comparisons between 7s and 15s which may guide risk mitigation strategies in managing brain trauma for specific forms of rugby.